(untitled) - Abrahams, Paul W. (Reading, Mass., 1992)
Topics include user utilities, shells, the vi editor and other standard editors, the GNU Emacs editor, Internet access tools, the awk language, the X Window System, and system administration from the user's perspective. Linux version of the DynaText browser not yet available
Keywords: Operating systems (Computers),UNIX (Computer file),Hệ điều hành (máy tính),UNIX (tập tin máy tính)